2021
DOI: 10.21037/tcr-21-679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of traditional laparotomy, extensive vaginal hysterectomy, and laparoscope-assisted vaginal hysterectomy in the treatment of patients with cervical intraepithelial neoplasia III

Abstract: Background: Cervical cancer is a common malignant tumor in women. This study aims to explore the clinical effects of traditional laparotomy, extensive vaginal hysterectomy and laparoscope-assisted vaginal hysterectomy in the treatment of patients with cervical intraepithelial neoplasia III (CIN III).Methods: A total of 79 cases with CIN III in situ who were treated in our hospital from July 2015 to February 2017 were selected as the study participants. According to the different surgical methods employed, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It has also been previously demonstrated that lycorine can inhibit the initiation and progression of cervical cancer. However, its underlying mechanism has not been determined (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been previously demonstrated that lycorine can inhibit the initiation and progression of cervical cancer. However, its underlying mechanism has not been determined (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%